Venture capital: Analysis of its evolution and emerging research trends - Reyes Ayala, Leonardo; Medina-Quintero, José Melchor; Morales Sáenz, Francisco Isaí; Ortiz Rodríguez, Fernando (Revista Venezolana de Gerencia, 2022)
Venture capital funds are crucial since they are a financing alternative for generating new companies. They also represent a series of critical resources that allow them to maintain improved performance in the target industry. The objective of this study is to carry out a bibliometric analysis on venture capital, through articles published within the Web of Sciences platform with indexing in the Journal Citation Reports, which identifies 1,653 research papers between 1980 and 2020. The results show the behavior and evolution of this topic in recent years, where there is a clear growing trend in venture capital research, as well as an overview of the authors and the most cited articles, including the production in terms of institutions, countries, and an analysis of the most used keywords by researchers, which represent an important area of opportunity for future studies related to this topic.